How Quality Control Systems AID Sec-Dependent Protein Translocation - Jiang, Chen; Wynne, Max; Huber, Damon (Frontiers in Molecular Biosciences, 2021)
The evolutionarily conserved Sec machinery is responsible for transporting proteins across the cytoplasmic membrane. Protein substrates of the Sec machinery must be in an unfolded conformation in order to be translocated across (or inserted into) the cytoplasmic membrane. In bacteria, the requirement for unfolded proteins is strict: substrate proteins that fold (or misfold) prematurely in the cytoplasm prior to translocation become irreversibly trapped in the cytoplasm. Partially folded Sec substrate proteins and stalled ribosomes containing nascent Sec substrates can also inhibit translocation by blocking (i.e. “jamming”) the membrane-embedded Sec machinery. To avoid these issues, bacteria have evolved a complex network of quality control systems to ensure that Sec substrate protein do not fold in the cytoplasm. This quality control network can be broken into three branches, which we have termed AID for: (i) avoidance of cytoplasmic intermediates through cotranslationally channelling newly synthesised Sec substrates to the Sec machinery; (ii) inhibition of folding Sec substrate proteins that transiently reside in the cytoplasm by molecular chaperones and the requirement for posttranslational modifications; (iii) destruction of products that could potentially inhibit translocation. In addition, several stress response pathways help to restore protein folding homeostasis when environmental conditions that inhibit translocation overcome the AID quality control systems.